Comparative Analysis of Hydrogenotrophic Denitrification in up and down Flow Reactors - Maharjan, Rabin; Amatya, Iswar Man; Sharma, Ram Kumar (Journal of the Institute of Engineering, 2019)
Use of ground water containing ammonical nitrogen has been increasing in Kathmandu valley. The use of locally and cheaply fitted Hydrogenotrophic Denitrification (HD) has been taken as an effective way to remove the nitrates in this study. Comparative analysis of HD reactors had been studied for the determination of the effective flow direction of water as Up Flow or Down Flow. The result reviled that flow direction as Down Flow HD reactor performed slightly better than Up Flow HD reactor. The maximum NO3-N conversion reached 100% for Down Flow and 98.65% for Up Flow reactor with maximum of total inorganic nitrogen (TIN) removed were 41.11% and 33.89% for Down Flow and Up Flow reactor respectively. The difference in NO3-N conversion and TIN removal were observed. As the NO2-N was accumulated, suggesting NO3 conversion is higher than NO2 conversion thus, and majorly incomplete denitrification existed. The NO2-N in water reached to maximum of 78.89 mg/l and 72.55 mg/l for Down Flow and Up Flow rector.